Mercenaries, pirates, and sovereigns : state-building and extraterritorial violence in early modern Europe - Thomson, Janice E., 1949- (Princeton studies in international history and politics., 1994)
The contemporary organization of global violence is neither timeless nor natural, argues Janice Thomson. It is distinctively modern. In this book she examines how the present arrangement of the world into violence-monopolizing sovereign states evolved over the six preceding centuries.